Circ_0072008, an oncogene in pancreatic ductal adenocarcinoma, contributes to tumour cell malignant progression and glycolysis by regulating miR-545-3p/SLC7A11 axis - Hui Sun; Fang Liu; Hongqing Zhang (Taylor & Francis Group, 2022)
Background The hsa_circRNA_103809 (circ_0072088) has been an emerging tumour regulator in human cancers, and is identified as one most aberrantly expressed circRNA in patients with pancreatic ductal adenocarcinoma (PDAC). However, the role of circ_0072088 remains unclear in PDAC cells. Methods Expression of circ_0072088, microRNA (miR)-545-3p and solute carrier family 7 member 11 (SLC7A11) was detected by real-time quantitative PCR and western blotting. Cell progression was measured by cell counting kit (CCK)-8 assay, transwell assays and flow cytometry, as well as xenograft tumour models. Glycolysis was evaluated by commercial assay kits. The interaction among circ_0072088, miR-545-3p and SLC7A11 was confirmed by dual-luciferase reporter assay. Results Circ_0072088 was upregulated in PDAC tumours and cells; besides, high circ_0072088 level was associated with high tumour-node-metastasis (TNM) stage. The circ_0072088 siRNA suppressed cell viability, migration, invasion, extracellular acidification rate (ECAR), lactate production, glucose uptake, and ATP generation, but promoted apoptosis rate and oxygen consumption rate (OCR) in SW1990 and PANC-1 cells. In vivo, circ_0072088 knockdown retarded tumour growth of PANC-1 cells. Overexpressing miR-545-3p mimicked circ_0072088 siRNA-induced actions, and inhibited cell progression and glycolysis of SW1990 and PANC-1 cells. Moreover, SLC7A11 downregulation could be mediated by both circ_0072008 siRNA and miR-545-3p mimic, and participating in suppressive role in cell progression and glycolysis of SW1990 and PANC-1 cells. In mechanism, miR-545-3p was targeted by circ_0072008, and SLC7A11 was target of miR-545-3p. Conclusion Circ_0072088 elicited oncogenic role in malignant cell progression and glycolysis of PDAC cells through circ_0072088/miR-545-3p/SLC7A11 pathway.Highlights Circ_0072088 was upregulated in PDAC tumours and was associated with high tumour burden. Blocking circ_0072088 suppressed cell proliferation, migration, invasion, and glycolysis in PDAC cells. Circ_0072088 could directly regulate miR-545-3p, and SLC7A11 was a target of miR-545-3p. Restoring miR-545-3p mimicked the effects of circ_0072088 knockdown in PDAC cell in vitro.